Talking Trade: Literacy Researchers as Practicing Artists - Albers, Peggy; Holbrook, Teri; Harste, Jerome C. (Journal of Adolescent & Adult Literacy, 2010)
Over the past two decades, educational scholars have seen major shifts in how literacy is viewed. One of these shifts has been toward conceptualizing literacy as a set of social practices (Street, 1995) that people embody and value. To disrupt current definitions of literacy, the valued practices that keep those forms of literacy in place must change. The authors have significantly changed their social practices to include personal, systematic, and continuous study of the arts, so much so that they identify both as literacy researchers and practicing artists. As such, their understanding of literacy has changed. This article presents the authors' thinking as artists and literacy researchers about meaning making, including their reflections on how working in the arts has impacted their perspectives on why the arts are significant to literacy practices. (Contains 7 figures.)
Keywords: bande dessinée; enseignement des arts; literacy

The Arts, New Literacies, and Multimodality - Albers, Peggy; Harste, Jerome C. (English Education, 2007)
The arts, multimodality, and new literacies studies, each with its own distinct principles, together can redefine literacy and what constitutes being literate. To recognize the roles that each of these fields plays in literacy necessitates a cultural shift in reading, interpreting, creating, and responding to a range of multimedia messages. The everyday literacies that learners bring to the classroom blur the lines between traditional literacy and unpredictable literacy, which promotes reading and writing through multimedia to create morphed and altered texts.
Keywords: arts; literacy; littératie visuelle; media literacy; théâtre